The Middle Stone Age of Nigeria in its West African context - Allsworth-Jones, P. (Archaeopress Publishing Ltd, 2019)
A fully up-to-date account of the evidence relating to the Middle Stone Age in Nigeria and the other countries of West Africa, based upon the author's own fieldwork and extensive personal knowledge of the region and its archaeology.